Treatment Outcomes of Transcatheter Closure in Common Congenital Heart Disease: Success Rate and Short-term Complications - Jittham, Worawan; Sanguanwong, Woranan (Biomedical Sciences and Clinical Medicine, 2022)
OBJECTIVE This study aimed to investigate treatment outcomes, including success rates and any short-term complications of transcatheter closure in common congenital heart disease (CHD), ventricular septal defect (VSD), atrial septal defect (ASD) and patent ductus arteriosus (PDA) at our tertiary cardiac center. METHODS This retrospective study was conducted at Naresuan University Hospital, Thailand. We enrolled patients for the analysis who had undergone transcatheter device closure (VSD, ASD and PDA) from October 2011 through May 2018. Treatment outcome success is defined as complete closure at 1 day, 1 month and 6 months following the procedure. Major complications associated with transcatheter device closure such as device embolization, arrhythmia, cardiac tamponade, thromboembolism, cardiac erosion and death were also collected. RESULTS Ninety-four patients, ranging from children to adults, were enrolled. ASD, PDA and VSD device closure was done in 45, 40 and 9 patients, respectively. Overall success at 1 day, 1 month and 6 months following the procedure were 87.3, 92.1 and 96.8%, respectively. There were 2 complications reported, one thromboembolism and one first-degree atrioventricular block (AVB). CONCLUSIONS Transcatheter closure in common congenital heart diseases provides good treatment outcomes and is safe for all age groups, from children to adults, with only a small number of major complications.